Comparative analysis between saliva and buccal swabs as source of DNA: lesson from HLA-B*57:01 testing. (July 2015) - Cascella, Raffaella; Stocchi, Laura; Strafella, Claudia; Mezzaroma, Ivano; Mannazzu, Marco; Vullo, Vincenzo; Montella, Francesco; Parruti, Giustino; Borgiani, Paola; Sangiuolo, Federica; Novelli, Giuseppe; Pirazzoli, Antonella; et al.
Aim: Our work aimed to designate the optimal DNA source for pharmacogenetic assays, such as the screening for HLA-B*57:01 allele.Materials & methods: A saliva and four buccal swab samples were taken from 104 patients. All the samples were stored at different time and temperature conditions and then genotyped for the HLA-B*57:01 allele by SSP-PCR and classical/capillary electrophoresis.Results: The genotyping analysis reported different performance rates depending on the storage conditions of the samples. Given our results, the buccal swab demonstrated to be more resistant and stable in time with respect to the saliva.Conclusion: Our investigation designates the buccal swab as the optimal DNA source for pharmacogenetic assays in terms of resistance, low infectivity, low-invasiveness and easy sampling, and safe transport in centralized medical centers providing specialized pharmacogenetic tests.